(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article examines the essence of creative thinking as an important professional quality of employees of internal affairs agencies. The features of professional activity requiring a non-standard approach to solving problems such as crime prevention and detection, interaction with citizens and analysis of complex situations are revealed. The main components of creative thinking are identified: analytical thinking, intuition, imagination and communication skills. It also provides recommendations for the development of creativity among employees through training, trainings and practical work in teams. The article emphasizes the importance of a creative approach to improve work efficiency in modern conditions.